LGG-19. LONGTERM EFFECT OF FIRST LINE CHEMOTHERAPY WITH VINCRISTINE AND CARBOPLATIN TO OPTIC PATHWAY GLIOMAS - Valiakhmetova, Andge (Neuro Oncol, 2018)
PURPOSE: Optic pathway gliomas (OPGs) compose a major therapeutic dilemma to the treating physicians. Prediction of late radiological response to Carboplatin-vincristine (CV) regime is still lacking. The aim of our study was to evaluate the long term effect 1(st) line chemotherapy. METHODS: 127 patients with OPGs were treated with CV regime chemotherapy from January 2003 to December 2016. The measurement of tumor volume included the delineation on each slice of the tomogram with the subsequent automatic calculation of the volume in the program OsiriX MD. For calculation of percentage of changing of the tumor we included the first MR study before initiation of treatment (X1) and control MRI at week 24 (X2), as the outcome study we included an imaging study that was done not less than 1 year, an average period of 4 years (range 1-10 years) following treatment termination (X3). Volume calculation followed to the formula (X3-X1(X2)/X1(X2)) x100%. RESULTS: A total of 103 patients from 127 met the inclusion criteria. 16 patients (12,5%) had PD, 35 SD (27,6%), 15 improvement (11,8%), 23 partial response (18%), and CR 14 (11%). In 4 patients CR was achieved at the time of completion of treatment. In 10 patients from 1 to 9 years after completion of treatment. CONCLUSIONS: Chemotherapy in treatment OPG is effective, achieving a complete response after 1(st) line CV regime of chemotherapy is possible in late time after completing of treatment. Future prospective trials with using molecular studies are needed to explanation and prediction of response to chemotherapy.